The Use of Lingoclip Application to Improve Students' Listening Skill at the Eight Grade of SMP 3 Bone - Alya Qur'annisa Monoarfa; Magvirah El Walidayni Kau; Helena Badu (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to investigate the effectiveness of the Lingoclip application in improving students’ listening skills at the eighth grade of SMP Negeri 3 Bone. This research employed a quantitative pre-experimental design using a pre-test and post-test to measure students’ listening comprehension before and after the treatment. A total of 26 students participated as the research sample. The treatment was conducted in four learning sessions using English songs integrated with the Lingoclip application. The findings show a significant improvement in students’ listening achievement, indicated by an increase in the total score from 1,240 in the pre-test to 1,795 in the post-test. The mean score also increased from 47.69 to 69.04, representing a remarkable improvement in listening performance. Furthermore, the result of the Paired Samples Test revealed a significance value of 0.000 (< 0.05), indicating that the Lingoclip application had a significant positive effect on students’ listening comprehension. These findings suggest that interactive, music-based digital media can effectively enhance students’ ability to identify gist, specific information, details, and inferences. Therefore, Lingoclip can be considered an effective supplementary learning tool for improving students’ listening skills and learning engagement.